Keefektivan Konseling Rational Emotive Behaviour Untuk Menurunkan Kejenuhan Belajar Siswa SMP - Retnowati Retnowati (ILIN Institute Makassar, 2018)
This study aims to test the effectiveness of rational emotive behavior to reduce the saturation of junior high school students. This research uses pre experimental pre-test type post test one group design. The data analysis used is paired sample test T-test. at a significant level ? = 0.05 (95%) then obtained t-table. = 1.812, assuming if t count> t-table then Ha